Somatotype and Ratio of Chest Circumference to Height in Asthma Patients and Its Relation to Asthma Control Level - Rosyadah, Prima Aprilia; Handayani, Selfi; Hastami, Yunia; Ghozali, Dhoni Akbar (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Asthma control level is related to body composition. Somatotype is a body shape classification that is used to measure body composition indirectly using anthropometry. As far as we know, no studies are related to somatotype and asthma control levels. This study aims to describe the somatotype and the ratio of chest circumference to height and its relation to asthma control level. Methods: This research is an observational study at Surakarta in September-December 2022. The subjects were 51 asthma patients under control and met the criteria. Measurement of somatotype and the ratio of chest circumference to height was carried out by anthropometric methods. The Asthma Control Test (ACT) questionnaire assessed the asthma control level. The collected data were analyzed using SPSS 26 software with Fisher’s test and unpaired t-test. Results: out of 51 asthmatic patients, 43 (84,3%) had endomorphic and 8 (15,7%) ectomorphic. Fisher’s test showed no significant relationship between somatotype and asthma control level (P=0.56). Meanwhile, the mean ratio of chest circumference to height in controlled patients was 0.54, while those who were uncontrolled were 0.58. The results of the unpaired t-test showed that there was a significant difference between the ratio of chest circumference to height and asthma control level (P=0.03). Conclusion: There is no significant relationship between somatotype and asthma control level, but there is a significant relationship between the ratio of chest circumference to height and the asthma control level.